Issues of Stage Space Organization in the System of Education of Future Choreographer - Portnova, Тatiana V. (Journal of Ecohumanism, 2024)
The article reveals the issues of spatial organization of a ballet performance and the specificity of compositional thinking of the future choreographer based on the spectacular nature of the theatrical image. We analyze the various components of spatiality created by the architectural environment of the stage, sculptural volume and angles of performers, color lighting, coloring, and linear perspective necessary for the competent and expressive construction of a choreographic work in the educational system. We analyze the educational methodology of compositional construction of the stage space: frontal, constructive, coloristic, and decorative levels, as shown by the most representative examples of the construction of ballet scenography created at the turn of the 19th–20th centuries. We emphasize the importance of studying and researching the spatial possibilities of the stage that enhance staging culture in the training process of choreographer directors.